Public Policy Innovation in Developing State Owned Business Agencies - Yeti Rohayati; Kurhayadi Kurhayadi (Universitas Djuanda, 2021)
State-owned Enterprise (BUMN), as one of the pillars of the Indonesian economy, is guided by the outline of the 1945 contusion and the existence of private entities and cooperatives. In principle, the state's involvement in these activities reflects the substance of article 33 of the amendment of the 1945 constitution. One of the missions of BUMN is to serve by innovating. Public policy innovating is a necessity that must be done to overcome problems that exist in society. From the point of view of public policy studies and public services, it can be seen that the government has developed several SOE development strategies that lead the country to face charges in the organizational environment and also to reduce the negative label attached to the bureaucracy. One of the goals of public policy innovation is to improve the quality of public services. The obstacle faced in public policy innovation is that there is no comprehensive study on the development and sustainability of policy innovation in public services in Indonesia